Development of Web-Based Tutorials For Online Databases - Anne M. Tubbs Prestamo (Issues in Science and Technology Librarianship, 1998)
A need for remotely accessible bibliographic instruction materials covering a variety of electronic databases has been identified. For the purposes of this project, and as a prototype for future development one database, ProQuest Direct (PQD), was selected as the subject for the development of a web-based tutorial.